Annual Plan Proposals 1973-74 Government of Kerala - Planning Commission (Planning Commission, 1973)
The Annual Plan proposals for 1973-74 have been prepared in accordance with the instructions contained in letter No. PC(P)2/72 dated 1st September 1972 from the Planning Commission. the outlay proposed for 1973-74 in the State sector is Rs. 75.66 crores. A provision of Rs. 12.88 crores is included to meet the expenditure on Centrally Sponsored Schemes. Thus the gross plan outlay during 1973-74 will be Rs. 88.54 crores. While drawing up these proposals, priority has been given to (a) Schemes to which Government are committed, (b) Spillover and incomplete schemes (c) completion of schemes which arc in a fairly advanced stage and (d) full utilisation of capacities created by plan investment in the past years.
Department of Planning and Economic Affairs Government of Kerala